Preoperative skin preparation: clinical evaluation of depilatory cream. Issue 6045 (13th November 1976) - Powis, S J; Waterworth, T A; Arkell, D G
Abstract : Preoperative hair removal by a depilatory cream was compared with routine shaving. Although the incidence of wound infection was similar in both groups, cream depilation was found to be better. It was effective, atraumatic, non-toxic, and could be self-administered. Furthermore, it could be used safely on granulating wounds and did not support bacterial growth. Depilation was associated with a significant reduction in skin surface bacteria and proved to be cheaper than shaving.